Interaction between equity futures and spot markets during COVID-19 pandemic: A multi-market analysis - Kalu O. Emenike (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2025)
Using ABA research design and daily indices from South Africa, Eurozone, Japan and the United States of America, this study evaluates the interaction between equity index futures and spot markets before; during and after the COVID-19 pandemic. The results show evidence of cointegration between the equity futures and spot markets before, during and after the COVID-19 pandemic, a unidirectional causal relationship from the equity spot to the futures markets before and after the COVID-19 era, and bidirectional causality between the equity spot and futures markets during the COVID-19 pandemic, except for the South African markets. The results also show evidence of more spikey volatility during the COVID-19 pandemic era than was the case before and after the pandemic and the existence of bidirectional volatility transmission between the markets. The magnitude of transmission was stronger from the spot to futures markets during the COVID-19 pandemic era. Overall, the results suggest that the interaction between equity futures and spot markets varies according to the prevailing economic condition and the level of development of the markets.
Keywords: G11; G13; G15; G32; 330; COVID-19 pandemic and equity markets; Futures-stock markets relationship; Price discovery; Volatility transmission